Micropartículas de metotrexato e ácido poli lático-co-glicólico obtidas por “spray-drying” - Garcia, Mirela Cardoso [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Methotrexate (MTX) is an antineoplastic agent of a short half-life, poorly soluble in water, alcohol, ether and chloroform, which affects your bioavailability. Poly lactic acid-co-glycolic acid (PLGA) is a biodegradable polymer that is hydrolyzed in the body, often used in controlled release system because of your characteristics the degradation. Microparticles PLGA / drug obtained by spray drying have been used in various pathologies, including anterior and posterior segment of the eye diseases. The aim of this study was to develop and characterize PLGA microparticles containing MTX obtained by spray-drying for a potential intraocular administration. PLGA microparticles containing MTX at two different concentrations were obtained. The morphology of the microparticles was spherical and the more drug is added, the particle tends to deform and the drug to be deposited on the particle surface. The infrared analysis (FTIR) suggest the occurrence of a physical mixture of PLGA and MTX, probably the interaction between carboxylic acids and amines present in MTX and the esters in PLGA molecule. The differential scanning calorimetry (DSC) and X-ray diffraction result that MTX is dispersed in the polymeric matrix with the prevalence of amorphous state, favoring the encapsulation efficiency (greater than 80%) and release, where PLGA microparticles containing 10% MTX showed sustained release profile after 72 hours, while containing 50% MTX characterize an initial burst effect and a slower release. The experimental results concludes successfully in obtaining microparticles PLGA containing MTX by spray drying and its potential as sustained drug release system may be interesting in treatment of eye diseases.

O metotrexato (MTX) é um antineoplásico de meia vida curta, pouco solúvel em água, álcool, éter e clorofórmio, o que compromete sua biodisponibilidade. O ácido poli lático-co-glicólico (PLGA) é um polímero biodegradável, que sofre hidrólise no organismo, comumente usado em sistema de liberação prolongada devido suas características de degradação. Micropartículas de PLGA/fármaco obtidas por spray-drying têm sido empregadas em diversas patologias, incluindo doenças do segmento anterior e posterior do olho. O objetivo deste trabalho foi desenvolver e caracterizar micropartículas de PLGA contendo MTX obtidas por spray-drying para potencial administração intraocular. Micropartículas de PLGA contendo MTX em duas diferentes concentrações foram obtidas. A morfologia das micropartículas demostraram-se de forma esférica e quanto mais se adiciona fármaco, a partícula tende a se deformar e o fármaco a se depositar na superfície da partícula. As análises de infravermelho (FTIR) sugerem a ocorrência de uma mistura física entre o PLGA e o MTX, provavelmente da interação entre os ácidos carboxílicos e aminas presentes no MTX com os ésteres da molécula do PLGA. A calorimetria exploratória diferencial (DSC) e difração de raios X resultam que o MTX está disperso na matriz polimérica com a prevalência de estado amorfo, favorecendo a eficiência de encapsulação (superior a 80%) e liberação, onde as micropartículas PLGA contendo MTX 10% obtiveram um perfil de liberação prolongada após 72 horas, enquanto as contendo 50% caracterizaram um efeito “burst” inicial e uma liberação mais lenta. Os resultados experimentais conclui êxito na obtenção das micropartículas de PLGA contendo MTX por spray drying e seu potencial como sistema de liberação prolongada de fármaco podendo ser interessante no tratamento ocular.
Keywords: Metotrexato; Secagem em spray; Farmacotécnica; Agentes antineoplasicos; Spray drying